Time‐frequency transform‐based differential scheme for microgrid protection. Issue 2 (1st February 2014) - Kar, Susmita; Samantaray, Subhransu Rajan
Abstract : The study presents a differential scheme for microgrid protection using time‐frequency transform such as S‐transform. Initially, the current at the respective buses are retrieved and processed through S‐transform to generate time‐frequency contours. Spectral energy content of the time‐frequency contours of the fault current signals are calculated and differential energy is computed to register the fault patterns in the microgrid at grid‐connected and islanded mode. The proposed scheme is tested for different shunt faults (symmetrical and unsymmetrical) and high‐impedance faults in the microgrid with radial and loop structure. It is observed that a set threshold on the differential energy can issue the tripping signal for effective protection measure within four cycles from the fault inception. The results based on extensive study indicate that the differential energy‐based protection scheme can reliably protect the microgrid against different fault situations and thus, is a potential candidate for wide area protection.